The access to the colonial archive in the second half of the XIX century: the Boletim e Annaes do Conselho Ultramarino - Henrique, Sónia Pereira (2019)
The Boletim e Annaes do Conselho Ultramarino (1854-1867) was a specialized journal of governmental sponsorship from which the Conselho Ultramarino was responsible for. The analysis of the publication sought to investigate the access to the Portuguese colonial archives, at the time. This made it possible to explore with some detail its role as a facilitator of an extended access to the overseas archives. The chronology of this study comprises the second half of the nineteenth century although the publication has recovered news and studies of a prior date.